Synthesis, characterization and catalytic activity of u-OXO bridged dinuclear iron 1,10-Phenanthroline incorporated in MCM-48 [compact disc] (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2006